2012
DOI: 10.31989/ffhd.v2i11.72
|View full text |Cite
|
Sign up to set email alerts
|

Agaricus blazei Murill - immunomodulatory properties and health benefits

Abstract: The Agaricus blazei Murill (AbM), also known as Agaricus brasiliensis L. due to its origin in Brazilian rain forest, is an edible mushroom of the Basidiomycetes family, which also comprises medicinal mushrooms such as Hericium erinaceus and Grifola frondosa. AbM has been used in traditional medicine locally and also recently as a health food worldwide. Since it has been found to possess immunomodulatory properties, its biological and health-related effects, as well as its isolated active ingredients e.g. beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 78 publications
(138 reference statements)
1
17
0
Order By: Relevance
“…However, the presence of Ehrlich tumor did not result in significantly increased levels in animals treated with WB7Poly, WB4Poly, WB4Sn, U7Poly, and U7Sn. Thus, the immunomodulatory activity of fungi described previously (BIEDRON et al, 2012) was partially observed in the present study. …”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…However, the presence of Ehrlich tumor did not result in significantly increased levels in animals treated with WB7Poly, WB4Poly, WB4Sn, U7Poly, and U7Sn. Thus, the immunomodulatory activity of fungi described previously (BIEDRON et al, 2012) was partially observed in the present study. …”
Section: Resultssupporting
confidence: 64%
“…Some of the functional compounds from A. blazei are inside the cell wall (FIRENZUOLI et al, 2008;BIEDRON et al, 2012). Therefore, greater disruption of the cells may increase adjuvant activity against cancers by releasing additional compounds.…”
Section: Introductionmentioning
confidence: 99%
“…AbM is rich in antitumor protein-glucan complexes [17], and β-glucans [18], which are potent stimulators of macrophages [19,20], granulocytes [21], natural killer (NK) cells [22] and DC [23]. The immunomodulatory properties and health effects of AbM have recently been reviewed [24].…”
Section: Introductionmentioning
confidence: 99%
“…They have been used to treat gastric cancer (lentinan) and head and neck cancer (schizophyllan), in combination with chemotherapy (Ina et al, 2013;Filipa et al, 2017). In addition, other polysaccharides rich in β-1, 3-D-glucans, β-1, 4-D-glucans, β-1, 6-D-glucans, α-1, 4-D-glucans, α-1, 6-D-glucans, and glucomannan have been isolated from A. blazei; these have been shown to have immunomodulatory and antineoplastic properties (Biedron et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies mentioned that most bioactive polysaccharides isolated from mushrooms are branched or unbranched homopolysaccharides (Biedron et al, 2012;Ina et al, 2013;Filipa et al, 2017), which usually contain long chains of glucose polymer. In our study, most of the mushroom extracts were positive with Molisch's test -a general test for detecting carbohydrates, including monosaccharides, disaccharides, and polysaccharides -indicating that the extracts contained carbohydrates.…”
Section: Discussionmentioning
confidence: 99%